KONSEPSI PROGRAM PARENTING ISLAM PADA MADRASAH IBTIDAIYAH - Maimun Maimun (STIT Sunan Giri Bima, 2023)
This research is a research on the development of an Islamic parenting program manual for Basic Education, and the development model used is in accordance with the characteristics of the target and the product being developed, namely the R & D Cycle development model developed by Borg & Gall (1983). The result achieved is a product in the form of an Islamic parenting program manual that is in accordance with the characteristics of Madrasah Ibtidaiyah in Mataram City. And the focus of this research are: (1) The process of designing a guidebook for the implementation of the basic education parenting program being developed; (2) The design of the guidebook for the implementation of the basic education parenting program developed; and (c) Implementation of the guidebook for the implementation of the basic education parenting program that was developed. The results of the research were in the form of a package of manuals for the implementation of the parenting program which began with a preliminary study at Madrasah Ibtidaiyah in the city of Mataram where the average welcomed the development of parenting manuals. The design of the guidebook for the implementation of the basic education parenting program is carried out through the following stages: Program socialization, formation of parenting program managers, equalization of perceptions with parents, identification of learning needs for parents, determination of place and time of activities, and preparation of programs and schedule of activities. While the stages in the implementation of the book being developed are: (a) Management of the Parenting Program; (b) The approach used; (c) Form of Parenting program; (d) Sources; (e) The method used; and (f) The role of the institution (Madrasah).